How I became a pirate - Long, Melinda; Shannon, David, 1959- (San Diego : Harcourt, 2003)
Jeremy Jacob joins Braid Beard and his pirate crew and finds out about pirate language, pirate manners, and other aspects of their life
Grades K-1
Keywords: Pirates -- Fiction